Modeling Analytical Ultracentrifugation Experiments with an Adaptive Space-Time Finite Element Solution for Multicomponent Reacting Systems - Cao, Weiming (The Biophysical Society, 2008)
We describe an extension of the adaptive space-time finite element method (ASTFEM) used in the solution of the Lamm equation to the case of multicomponent reacting systems. We use an operator splitting technique to decouple the sedimentation-diffusion process from the reaction process. The former is solved with an ASTFEM approach based on the Petrov-Galerkin method and on adaptive moving grids, and the latter is solved with the implicit midpoint Euler's method. Our solution can effectively eliminate the sedimentation errors for each component or species involved in the reaction, and it is free from oscillation near the cell bottom. It offers second-order accuracy, and guarantees conservation of mass without any additional postprocessing, and it permits modeling of multicomponent, equilibrating systems where the reaction rate can be kinetically controlled between an instantaneous reaction and a noninteracting mixture. The proposed ASTFEM solution provides improved efficiency and accuracy compared to classical approaches, especially when medium-sized and large molecules are modeled.